Effect of dietary resveratrol on placental function and reproductive performance of late pregnancy sows - Hu, Ruizhi; Tan, Jijun; Li, Zhanfeng; Wang, Long; Shi, Mingkun; Li, Baizhen; Liu, Ming; Yuan, Xupeng; He, Jianhua; Wu, Xiaosong (Frontiers in Nutrition, 2022)
Placental function is vital to fetal growth in late pregnancy of sows, and resveratrol can protect cells against oxidative stress, which is one of the major factors impairing placental function. This study aimed to investigate the effect of dietary resveratrol on placental function and reproductive performance of sows during late pregnancy from the aspect of oxidative stress, insulin resistance and gut microbiota. A total of 26 hybrid pregnant sows (Landrace × Yorkshire) with similar parity were randomly allocated into two groups (n = 13) and fed with a basal diet or a diet containing 200 mg/kg of resveratrol from day 85 of gestation until parturition. Dietary supplementation of resveratrol decreased the stillbirth and increased the litter weight at parturition by 12.53% (P= 0.145), with ameliorated insulin resistance (HOMA-IR), increased triglyceride (TG) level and decreased interleukin (IL)-1β and IL-6 levels in serum (P< 0.05). Moreover, resveratrol increased the placental vascular density (P<0.05) with enhanced expression of nutrient transporters genes (SLC2A1 & SLC2A3) and antioxidant genes including superoxide dismutase 2 (SOD2) and heme oxygenase-1 (HO-1), but declined expression of inflammatory genes including IL-1β and IL-6 (P<0.05). Characterization of fecal microbiota revealed that resveratrol decreased the relative abundance of Christensensllaceae R-7 group and Ruminococcaceae UCG-008 (P<0.05), which had a positive linear correlation with the expression of IL-1β and IL-6 (P<0.05), but had a negative linear correlation with the expression of SOD2, HO-1, SLC2A1 and SCL2A3 genes (P<0.05). These data demonstrated that dietary supplementation resveratrol can improve placental function with ameliorated insulin resistance oxidative stress and inflammation potentially by regulating Ruminococcaceae UCG-008 and Christensensllaceae R-7 group in sows.